Australian health care workers experience of PPE related side-effects. A cross-sectional survey - Karen McKenna; Karen McKenna; Stephane Bouchoucha; Stephane Bouchoucha; Stephane Bouchoucha; Stephane Bouchoucha; Bernice Redley; Anastasia Hutchinson; Anastasia Hutchinson; Anastasia Hutchinson (Frontiers Media S.A., 2024)
IntroductionProtection of health care workers (HCWs) is a fundamental aspect of an effective pandemic response. During the COVID-19 pandemic, frequency, and duration of Personal Protective Equipment (PPE) use increased. The experience of PPE-related side-effects has potential to contribute to decreased compliance resulting in breaches in infection prevention and increasing risk of HCW exposure. This study aims were to measure the frequency of PPE-related side-effects amongst HCW in Australia, and to establish if an increased frequency of adverse reactions was related to the significant increase in use and extended duration of time spent in PPE.MethodsA descriptive cross-sectional survey was used.ResultsOf the 559 respondents the majority were female (83.7%), aged 31-45 years old (33.6%). A pre-existing skin condition was reported by 266 (47.6%). Frequency of PPE related side-effects were: pressure-related 401 (71.7%), skin 321 (57.4%) and respiratory 20 (3.6%). Surgical mask use was significantly associated with pre-exiting skin conditions (β = 1.494 (SE 0.186), df (1), p < 0.001). Side effects to N95 respirator use was more commonly reported by staff working in COVID-19 high-risk areas (β = 0.572 (SE 0.211), df (1), p = 0.007) independent of work duration (β = −0.056 (SE 0.075), df (1), p = 0.456), and pre-existing skin conditions (β = 1.272, (SE.198), df (1), p < 0.001).ConclusionThe COVID-19 pandemic has seen a significant increase in the use of PPE. While the preventative benefits of PPE are significant, adverse events related to PPE use are frequently reported by HCW. Findings in this study highlight the need for innovation in PPE design to maximize protection while decreasing adverse effects and maintaining adhere to use.